Diagnostic Challenge in Distinguishing Crohn’s Disease from Lupus Enteritis in Systemic Lupus Erythematosus Patient: A Case Report - Layadi, Eka Benhardi; Pribadi, Rabbinu Rangga; Ariane, Anna; Kartika, Emiliana; Handjari, Diah Rini; Idzni, Irsalina; Ichsan, Oemar; Putri, Megawati Ananda Hasbi (The Indonesian Society for Digestive Endoscopy, 2023)
Diagnosing Crohn’s disease in systemic lupus erythematosus patients with gastrointestinal symptoms poses a great challenge, due to its rare occurrence and similarity of clinical characteristics between its differential diagnosis. We herein present a rare case of a patient diagnosed with systemic lupus erythematosus, complicated by renal involvement and conspicuous gastrointestinal manifestations. The non-specific gastrointestinal findings in this patient led to challenge in differentiating lupus enteritis from Crohn's disease, as they share many similar aspects in clinical manifestations, endoscopic findings, and histopathological findings. We herein provide the clinical judgement in reaching Crohn's disease in concurrence with systemic lupus erythematosus as the final working diagnosis through scrutinizing and comparing data from similar case studies in the past.